Building bridges to protect health - Harvey, Hillery (New Zealand Science Review, 2011)
​This paper describes work under a Fellowship in Public Policy centred on enhanced partnerships among human, animal, and ecosystem health sectors in New Zealand. The outcome of the project is a guide to help protect the health of New Zealand’s people, production animals, wildlife, and environment by urging and guiding transdisciplinary interactions (Harvey 2010a).